The role of private authority in global governance frameworks: the case of the climate knowledge infrastructure in the era of big data - Almeida, Matheus Moreira Alves (2024)
Climate change is regarded by many scholars and activists as the most pressing challenge of the twenty-first century. Given the dire consequences of the issue over many aspects of political, economic, and social life on earth, this subject requires a multifaceted and interdisciplinary approach to tackle both its causes and effects. In this effort, this work resorts to the debate around global governance and the concept of climate knowledge infrastructure, two independent, yet complimentary literatures that can offer a powerful analytical framework to assess the political economy around climate change. The goal of this research is twofold: introduce the theoretical reasoning as to why both literatures can mutually benefit from their contributions and lay out how a multistakeholder coalition against climate change has been enabled by the emergence of new digital technologies. Through an abductive analysis process, this research argues for the importance of establishing solid public-private partnerships in providing reliable and accurate weather and climate products, such as weather forecasts and early warning services.